GRAMMATICAL ERRORS ON ARTICLE USAGE IN EFL STUDENTS’ WRITING OF REPORT TEXT - Adi Yusuf; Rizqi Lestari (Fakultas Komunikasi, Sastra, dan Bahasa, 2023)
Articles are one of the most difficult parts in writing, especially for EFL students. Different use of articles often leads the students to make errors. This study is intended to know the types of article errors made by students in writing report text and to explain why the errors occur. This study used a descriptive qualitative method. The subjects of this study were the students of class nine at X Junior High School in Jombang. Based on the analysis, it had been found that there were 3 types of article errors: the definite article, the indefinite article, and no article. The results of this study indicated that the students made errors on all types of articles. The errors happened because of both interlingual transfer and intralingual transfer. Finally, it can be concluded that the students had a lack of knowledge in English articles.